Blood profile and nutrients digestibility of native chickens fed functional diets with different energy and protein level. Issue 1 (June 2021) - Hafsah,; Sarjuni, S; Mozin, S; Fatmawati,; Malewa, A; Sucipto, I N; Saifuddin, S
Abstract: This study aimed to determine the blood profile, pH value of the small intestine and nutrient digestibility of native chickens fed functional diets with different energy and protein levels. The study used 192 DOC of native chickens with rearing up to 14 weeks old. The study was designed in a factorial completely randomized design with two factors. The first factor was the energy level (E1 = 2, 800 kcal, E2 = 3, 000 kcal), and the second factor was the protein level (P1 = 18%; P2 = 19%; P3 = 20%; P4 = 21%), each treatment had 4 replications. The feed ingredients used as functional feed in the ingredients of the ration i.e. yellow corn, rice bran, fish meal, soybeans grain, moringa leaves flour, turmeric flour, and Topmix® with the feed composition according to the treatment applied. Blood sampling, measurement of pH duodenum segment of the small intestine, and measurement of nutrient digestibility were performed on chickens after 12 weeks of age. The variables observed were blood profile, small intestinal pH, and nutrient digestibility. Data were analyzed using analysis of variance according to the design applied. The results showed that the effect of interaction between energy and protein level had a non-significant effect (P>0.05) on blood profile (hemoglobin, leucocyte, erythrocytes, platelets), small intestine pH, and nutrient digestibility. Similarly, also found the influence of a single factor of each energy and protein level. However, the treatments influenced a significant effect (P<0.05) on hematocrit and blood bilirubin values, and a highly significant effect (P<0.01) on total blood cholesterol. The study concluded that energy levels and protein levels had influenced significantly on blood profile, but not in pH intestine and nutrient digestibility.